Relevansi Verbal Bulliying dengan Kecerdasan Interpersonal Siswa - Nurul, Nurul Fitri; Sari, Rita; Rahayu, Nina (azkiya, 2022)
Some children often express mockery words known as verbal bullying. Verbal expressions of bullying are words of ridicule that can offend others. This study aims to determine the relationship between verbal bullying and the interpersonal intelligence of elementary level students in Gampong Teungoh Langsa. The method used in this study is a quantitative method to see the relationship between verbal bullying and interpersonal intelligence. Hasil of this study states that 1) The form of verbal bullying that occurs in children in Gampong Teungoh in 2021 is mocking, mentioning parents' names, giving inappropriate nicknames to friends such as the name of the comedian doyok, dono because his friend's teeth are boneng. This form of bullying is called verbal bullying, which is a form of bullying in the form of inappropriate words to be expressed to others. 2) The level of interpersonal intelligence can be seen from the results of the normality test that the significance value is 0.544 > 0.05. Then it can be concluded that the residual value is normally distributed. 3) The relationship between verbal bullying and interpersonal intelligence where the correlation of the relationship between verbal bullying and interpersonal intelligence is a perfect correlation where the correlation value amounts to 0.998. This indicates that the higher the child's interpersonal intelligence, the higher his personality.